Studies of functionalized scaffolds for cardiovascular tissue engineering - Ang, Hui Ying (2015)
The study described here has made considerable progress in developing techniques and optimizing materials for fabricating a cellularized and bioactive construct for use in cardiovascular tissue engineering. In the engineering of cardiac construct with volume to have clinical relevance, the issue of vascularization is of considerable importance. The envisioned construct in this study consists of an endothelial cell bearing module and electrospun PCL fibers that can secrete pro-angiogenic factors to enhance vascularization. Firstly, the cytocompatibility of PCL was characterized with and without modification. PCL scaffolds were fabricated using electrospinning and dip coating techniques. The attachment, proliferation and stemness of mesenchymal stem cells (MSCs) were studied on electrospun PCL. It was found that the scaffold was able to support the growth of MSCs, which retained their stemness after a week’s culture. Surface modification with 1M sodium hydroxide (NaOH) and crosslinking of gelatin using 1-Ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC) was performed on dip coated PCL tubular scaffolds. The surface modification led to increased PCL hydrophilicity and improved the attachment and proliferation of human umbilical vein endothelial cells (HUVECs) within the lumen of tubular scaffold. Physiological conditions demonstrated that the modifications increased HUVECs retention on PCL. Subsequently, a bioactive scaffold of hollow fibers with entrapped cells secreting growth factors was fabricated. The coaxial electrospinning process was optimized, ensuring the consistent formation of PEO(core)-PCL(shell) fibers. PEO solution supplemented with Fetal bovine serum (FBS) improved the viability of electrospun cells. The electrospinning of HUVECs acted as a “proof of concept”, showing the deposition of intact and viable cells within PCL electrospun. As HUVECs secrete interleukin-8 (IL-8), enzyme-linked immunosorbent assay (ELISA) was performed to demonstrate the release of biomolecules from entrapped HUVECs. IL-8 was detected in the medium surrounding electrospun fibers, suggesting that the entrapped cells were able to play a paracrine role. To test the concept, HEK 293T cells were transfected with pVEGF-165 construct and electrospun. The cells were found to proliferate within the fibers, managing a 40-fold growth by 2 weeks. Furthermore, the surrounding medium tested positive for secreted VEGF. Finally, a composite construct consisting of the endothelialized tubular scaffold and bioactive fibers sandwiching a transglutaminase-crosslinked gelatin hydrogel was fabricated. This formed a stable construct, as the SEM images showed good interactions between the electrospun fibers, tubular scaffold and central hydrogel. Indeed, the constructs were able to maintain more than 50% of their original weight and there was no significant delamination of the hydrogel from the synthetic scaffolds after 14 days in culture media with/without mechanical agitation. It was observed that MSCs seeded on the electrospun PCL of the composite construct had a reduced growth rate, but still proliferated and reached a 5.8-fold growth after 12 days. Next, the effect of bioactive fibers releasing VEGF on HUVECs within the 3D environment was assessed. The results revealed that the VEGF increased HUVEC viability after 2 days. Taken together, the results suggested that the functionality of synthetic PCL scaffold can be improved with surface modification and entrapment of cells secreting growth factors. The delivery of growth factors such as VEGF can enhanced the growth of HUVECs, which could be beneficial in terms of angiogenesis.